Alterations in erythrocyte membrane transporter expression levels in type 2 diabetic patients - Edit Szabó (Nature Portfolio, 2021)
Abstract Type 2 diabetes mellitus (T2DM) is one of the most common multifactorial diseases and several membrane transporters are involved in its development, complications and treatment. We have recently developed a flow-cytometry assay panel for the quantitative determination of red cell membrane protein levels with potential relevance in diseases. Here we report a detailed phenotypic analysis of a medium scale, clinically based study on the expression of T2DM-related membrane proteins, the GLUT1, GLUT3, MCT1, URAT1, ABCA1, ABCG2 and the PMCA4 transporters in erythrocytes. By comparing age-matched control subjects and three groups of T2DM patients (recently diagnosed, successfully managed, and patients with disease-related complications), we found significant differences in the membrane expression levels of the transporters in these groups. This is a first detailed analysis of T2DM related alterations in erythrocyte membrane transporter protein levels, and the results suggest significant changes in some of the transporter expression levels in various patient groups. By performing a further, more detailed analysis of the clinical and molecular biology parameters, these data may serve as a basis of establishing new, personalized diagnostic markers helping the prevention and treatment of type 2 diabetes.